Pengaruh Fee Audit terhadap Kualitas Audit dengan Komite Audit sebagai Variabel Moderasi pada Perusahaan Perbankan yang Terdaftar di Bei Periode 2021-2024 - Abelia Fajroyur Rohman; JB Amiranto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study, entitled An Empirical Analysis of Indonesian Stock Exchange-Listed Financial Sector Companies for the 2021–2024 Period, investigates the effect of audit fees on audit quality with the audit committee as a moderating variable. The research population consisted of 46 financial sector companies listed on the Indonesia Stock Exchange, while the sample comprised 29 companies selected through purposive sampling based on predetermined criteria. This study employed panel data analysis using EViews 12, with Moderated Regression Analysis as the analytical model to examine both the direct effect and moderating role of the audit committee. The results show that audit fees do not have a significant effect on audit quality. Furthermore, the audit committee is unable to moderate the relationship between audit fees and audit quality. Therefore, both proposed research hypotheses are rejected. These findings indicate that, within financial sector companies, audit quality is not necessarily determined by the amount of audit fees paid or by the presence of an audit committee. Other factors outside the scope of this study may have a stronger role in explaining audit quality during the period.